Thermostability and weatherability of TiN/TiC-Ni/Mo solar absorption coating by spray method-laser cladding hybrid deposition. (April 2020) - Pang, Xuming; Zhou, Fulin
Highlights: The cermets solar absorber coatings were firstly prepared by spray method-laser cladding hybrid deposition. Compared with typical the multi-scale cermets and the multilayer structure, a high-performance coating, a new single-layer TiC/TiN-based single-layer structure, were designed and fabricated. The single-layer TiC/TiN-based cermets coating has excellent the long-term thermal stability. Three dimensional temperature field model of coating was first established for laser cladding method. The dilution rate was researched by the theory and experiment, which directly influences the weather resistance of the coatings. Abstract: A novel one-layer micrometre-sized TiC/TiN-based spectrally selective coating was designed and fabricated via spray method-laser cladding hybrid deposition in air. The laser cladding was used to obtain TiC/TiN-Ni/Mo cermet coatings with desirable optical properties. In particular, an absorptance (α) of ~84% and thermal emissivity (ε) of ~5% at 300 K were calculated at a TiC/TiN weight ratio of 1:1. In addition, the thermal stability of the coating was outstanding after heat treatment at 650 °C for 200 h. The absorptance and emissivity of the 30 wt.% TiC-30 wt. %TiN-20 wt.% Ni-20 wt.% Mo cermet coatings were respectively 82% and 4%, respectively, at 650 °C. Furthermore, the cermet coating also exhibited excellent weatherability, indicateing that TiC/TiN-based cermets are suitable for spectrally selective materials. Moreover, the laser cladding was demonstrated as an improved and novel preparation technology for manufacture of solar selective absorbing coatings.